2006
DOI: 10.1037/0735-7044.120.5.1144
|View full text |Cite
|
Sign up to set email alerts
|

Conditioning following repeated exposure to MDMA in rats: Role in the maintenance of MDMA self-administration.

Abstract: There has been some controversy in the literature concerning the ability of +/-3,4 methylenedioxymethamphetamine (MDMA) to reinforce operant responding in rats. In the present study, operant responding maintained by intravenous MDMA infusions increased when the fixed ratio schedule was increased from 1 to 5, decreased when saline was substituted for MDMA, and increased again when MDMA was reintroduced. During self-administration training, each infusion of MDMA was paired with the illumination of a light stimul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
33
1

Year Published

2008
2008
2016
2016

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(34 citation statements)
references
References 69 publications
(88 reference statements)
0
33
1
Order By: Relevance
“…Hence, a decline in its reinforcing properties has been observed in monkeys self-administering the drug for 18 months (Fantegrossi et al 2004). However, in rats self-administering high doses of MDMA (0.25-1.0 mg/kg per infusion), no reduction in reinforcing effects was apparent (Schenk et al 2003;Daniela et al 2004Daniela et al , 2006. Thus, there are still no clear data as to whether self-administered MDMA produces changes in reward-related behavior.…”
mentioning
confidence: 80%
“…Hence, a decline in its reinforcing properties has been observed in monkeys self-administering the drug for 18 months (Fantegrossi et al 2004). However, in rats self-administering high doses of MDMA (0.25-1.0 mg/kg per infusion), no reduction in reinforcing effects was apparent (Schenk et al 2003;Daniela et al 2004Daniela et al , 2006. Thus, there are still no clear data as to whether self-administered MDMA produces changes in reward-related behavior.…”
mentioning
confidence: 80%
“…If so, this would explain the apparent resistance to extinction that we had informally observed. This was formally tested [67] by first providing substantial self-administration experience to a group of rats. The influence of the continued presentation of a light stimulus that had been associated with self-administered MDMA infusions on lever pressing behavior was measured.…”
Section: Maintenance Of Mdma Self-administration In Laboratory Animalsmentioning
confidence: 99%
“…There is also evidence that the interoceptive stimuli produced by MDMA in rats are different from those of other psychostimulants, at least from cocaine [33] . There is some proof that MDMA self-administration can be tied to environmental cues such as a light signal or increased ambient temperature [30,[34][35][36] . Cornish et al [34] showed, in the rat, that a relatively warm temperature (30 ° C) increased MDMA self-administration as compared to a lower temperature (21 ° C).…”
Section: Mdma Has a Unique Pharmacological Profilementioning
confidence: 99%
“…Cornish et al [34] showed, in the rat, that a relatively warm temperature (30 ° C) increased MDMA self-administration as compared to a lower temperature (21 ° C). In the approach reported by Daniela et al [35] , self-administration training was based on pairing an infusion with a light stimulus. Omitting the light stimulus in the selfadministering rats resulted in a gradual decrease in operant responding.…”
Section: Mdma Has a Unique Pharmacological Profilementioning
confidence: 99%